Analysis of Factors Related to Burnout among Nurses in Inpatient Rooms - Susan Irawan Rifai; Dedep Nugraha (Indonesian Journal of Global Health Research, 2026)
Burnout is physical, emotional, and mental exhaustion experienced by nurses due to prolonged work stress.  This condition has a negative impact on the quality of health services, increases the risk of work errors, and reduces the efficiency of patient care. There are several factors that influence the occurrence of burnout in nurses, including nurse characteristics, family support, and workload. The purpose of this study is to Analysis of Factors Related to Burnout Among Nurses in Inpatient Rooms. This study uses a quantitative descriptive research design with a cross-sectional approach. A total of 68 practicing nurses will participate in this study. The research instrument used a questionnaire consisting of a questionnaire on nurse characteristics (age, gender, length of service, education level, marital status, and employment status), a questionnaire on family support, workload, and burnout in nurses. Data analysis will use frequency distribution, chi-square, and multiple linear regression tests. The results show that age (p=0.038), education level (p=0.040), and workload (p=0.025) are significantly related to burnout in nurses, while gender (p=0.808), length of service (p=0.24), marital status (p=0.235), and family support (p=302) were not associated with burnout among nurse. These results indicate that young nurses, have a high level of education and a high workload are more likely to experience burnout. Therefore, there is a need for routine monitoring of stress and burnout levels among nurses, especially among young and newly employed nurses. Additionally, there is a need for stress management training, psychosocial support, and counseling rooms for nurses who show symptoms of fatigue or burnout.